PENGARUH PASSIVE LEADERSHIP TERHADAP BEHAVIORAL INCIVILITY DENGAN EXPERIENCED WORKPLACE INCIVILITY SEBAGAI VARIABEL MEDIASI PADA KANTOR DINAS PEMERINTAH KOTA BANDA ACEH - Winda Tri Ulandari, Nasrillah Anis (Jurnal Ilmiah Mahasiswa Ekonomi Manajemen, 2016)
The aims of this study are to investigate the effect of store environment, hedonic consumption tendency and positive emotion on impulse buying. The consumers of Matahari Hermes Palace Mall Banda Aceh is taken as a sample in this study. The method of this study employed questionnaires as an instrument. Total sampling is applied as the study’s convenience technique. Hierarchical Linear Modeling methods of analysis are used to determine the influence of the variables involved. The result of this study indicates that store environment, and hedonic consumption tendency have positive effect on impulse buying, store environment, and hedonic consumption tendency have positive effect on positive emotion, and positive emotion has positive effect on impulse buying. The study also shows that store environment, hedonic consumption tendency influential significantly against positive emotion nor against impulse buying. In addition obtained results that positive emotion has full/perfect mediated the effect of store environment, hedonic consumption tendency to impulse buying.Keyword : Passive Leadership, Experienced Workplace incivility, Behavioral Incivility.